Fungsi Gramatika Frasa Numeralia dalam Kalimat Bahasa Melayu Jambi - Ade Rahima (Universitas Batanghari Jambi, 2022)
The purpose of this study is to describe the grammatical function of Jambi Malay numeral phrases (BMJ). The method used in this research is descriptive method. Sources of research data include oral data derived from informants and written data taken from a collection of Jambi folklore. Overall, this research was conducted in two locations, namely Muaro Jambi Regency and Jambi City. Research data in the form of BMJ phrases and sentences. Data collection techniques used include interview, observation, introspection, and elicitation techniques. Data analysis was done by distributional method through substitution, expansion and permutation techniques. The results of data analysis show that the grammatical functions of FNum in the BMJ sentence structure include subject, predicate, object, and adverb.